The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18632/aging.203541
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated m6A modification of KIF3C-mRNA promotes prostate cancer progression and is negatively regulated by miR-320d

Abstract: The occurrence of distant metastasis is one of the leading causes of death in patients with prostate cancer (PCa). It is confirmed that kinesin protein is associated with a variety of malignancies, and the KIF3 family is related to cancer, but the relationship between KIF3C and prostate cancer is not clear. Our experiments have confirmed that KIF3C is highly expressed in prostate cancer tissues and cell lines. Further, functional tests have proven that KIF3C can promote the growth migration and invasion of PCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…A later study also shows that IGF2BP1 promotes tumorigenesis and metastasis of oral squamous cell carcinoma via enhancing Bmi1 mRNA translation in METTL3-mediated m 6 A modification manner 146 . A subsequent study shows that METTL3 promotes the mRNA stability of kinesin-like protein, KIP3C in IGF2BP1- modified m 6 A manner, accelerating prostate cancer progression 147 . Moreover, METTL3 methylates KRT7-AS to enhance the mRNA stability of keratin 7 (KRT7) depending on IGF2BP1-modified m 6 A, promoting breast cancer lung metastasis 148 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 95%
“…A later study also shows that IGF2BP1 promotes tumorigenesis and metastasis of oral squamous cell carcinoma via enhancing Bmi1 mRNA translation in METTL3-mediated m 6 A modification manner 146 . A subsequent study shows that METTL3 promotes the mRNA stability of kinesin-like protein, KIP3C in IGF2BP1- modified m 6 A manner, accelerating prostate cancer progression 147 . Moreover, METTL3 methylates KRT7-AS to enhance the mRNA stability of keratin 7 (KRT7) depending on IGF2BP1-modified m 6 A, promoting breast cancer lung metastasis 148 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 95%
“…We found that KIF3C expression was upregulated in non-small cell lung cancer cells and tissues and promoted the proliferation and metastasis of lung cancer cells. The expression of KIF3C was also found to be negatively regulated by miR-150-5p and miR-186-3p [19] . Dysregulation of PI3K/AKT signaling pathway has been demonstrated in both, tumor and non-tumor diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Prostate cancer is the second most common cancer in men and the fifth leading cause of cancer deaths, with approximately 1.4 million new cases and 375,000 deaths each year [ 176 ]. Studies showed that METTL3 regulates LEF1 [ 199 ], KIF3C [ 200 ], USP4 [ 201 ], GLI1 [ 202 ], ITGB1 [ 170 ], IGF1R [ 203 ], and lncRNA PCAT6 [ 203 ] expression in an m6A-dependent manner to promote prostate cancer malignant progression. One study showed that knocking out METTL3 drives prostate cancer cell resistance to androgen receptor antagonists; hence, the change in m6A abundance may be a mechanism underlying treatment resistance in metastatic prostate cancer [ 43 ].…”
Section: M6a and Cancersmentioning
confidence: 99%